Potential role of serological biomarkers in the diagnosis and prediction of community-acquired pneumonia in elderly individuals - Hou, Chen; Jin, Yi Feng; Li, Jie (Frontiers in Medicine, 2025)
Community-acquired pneumonia (CAP) is one of the most common lower respiratory tract infections (LRTIs) and has substantial clinical and economic impacts on healthcare systems worldwide. Because of impaired host defenses and/or underlying health problems, CAP in elderly patients is associated with increased mortality and morbidity compared with that in younger patients and is prone to developing severe community-acquired pneumonia (SCAP). Diagnosis, severity evaluation, and prognosis are still challenges for physicians. Therefore, new diagnostic methods are needed to identify the different stages of CAP and monitor disease progression. The value of serological biomarkers has been extensively investigated in infectious diseases. In clinical practice, there are currently no defined or agreed-upon biomarker(s) for CAP that can be readily tested. An ideal biomarker that is simple, easy to perform, noninvasive or microinvasive, inexpensive, rapid, and reproducible is helpful for patients and clinicians. The aim of this review is to highlight potential serological biomarkers for the diagnosis and prediction of CAP in elderly individuals, providing novel strategies for patient stratification and treatment.